PENGARUH SLOW DEEP BREATHING (TEKNIK NAFAS DALAM) TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI DI PUSKESMAS NEGERI BARU KECAMATAN UMPU SEMENGUK KABUPATEN WAY KANAN TAHUN 2023 - Annisa Agata; Nova Nurwinda Sari; Allan Arisyandi (MOTORIK Jurnal Ilmu Kesehatan, 2024)
year to year. Hypertension can be treated pharmacologically and non-pharmacologically, one of which is slow deep breathing. The aim of this research is to determine the effect of slow deep breathing on blood pressure in hypertension sufferers at the Negeri Baru Health Center, Umpu Semenguk Way Kanan District in 2023. This type of quantitative research, the design in this research uses a Quasi Experimental design using the One Group Pretest – Posttest Design approach. The population in this study were 177 people suffering from hypertension at the Negeri Baru Community Health Center, Umpu Semenguk Way Kanan District, as of September 2023 and a research sample of 61 respondents. The sampling technique in this research was purposive sampling. Based on statistical tests, the T test obtained a p-value of 0.000, or p-value < 0.05, so it can be concluded that there is an effect of slow deep breathing on blood pressure in hypertension sufferers at the Negeri Baru Health Center, Umpu Semenguk District, Way Kanan Regency. It is hoped that the results of this research can provide health information for respondents at the Negeri Baru Health Center, Umpu Semenguk District, Way Kanan Regency. In order to apply slow deep breathing regularly every day, so that the respondent's blood pressure is well controlled